To solve the equation \(3(2x+2) - 4 = -2x + 10\), we can follow these steps:
-
Distribute the 3 on the left side: \[ 6x + 6 - 4 = -2x + 10 \] Simplifying the left side gives: \[ 6x + 2 = -2x + 10 \]
-
Add \(2x\) to both sides: \[ 6x + 2x + 2 = 10 \] This simplifies to: \[ 8x + 2 = 10 \]
-
Subtract 2 from both sides: \[ 8x = 10 - 2 \] Simplifying gives: \[ 8x = 8 \]
-
Divide both sides by 8: \[ x = 1 \]
Now, let's determine the nature of the solution:
- Since we found \(x = 1\), the equation has one solution.
The answer is: The equation has one solution: \(x = 1\).